Relationship between Physiological Characteristic and Bean Quality on Some Cocoa Clones (Theobroma cacao L.) - Indah Anita Sari; Fakhrusy Zakariyya; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2015)
Photosynthesis is one of the physiological process that influence the bean weight and this process related with the efectiveness of the stomata character and chlorophyll content in the leaves. The research was conducted at Kaliwining Research Station, Indonesian Coffee and Cocoa Research Institute. Design of experiment was randomized complete block design (RCBD) consisted of six clones as treatment were Sulawesi 1, Sulawesi 2, Sca 6, ICS 60, TSH 858, ICCRI 03, PA 300. Each treatment was replicated three times. Stomata resistance diffusion, tranpiration,the content of chlorophyll a, chlorophyll b, chlorophyll total (a+b), bean number and bean weight were observed. The resuts of experiment showed that difference in chlorophyll a, chlorophyll b, chlorophyll total (a+b), stomata resistance diffusion, bean number and bean weight existed within six clones tested. Transpiration rate did not show the significantly different between six clones tested. Sulawesi 1 showed the highest content of chlorophyll a and ICS 60 and ICCRI 03 showed higher content of chlorophyll b than the other clones. Chlorophyll a, b and total (a+b) showed positively influence on bean number and bean weight. Transpiration rate had negatively influence to bean number per pod, on the otherhand it showed positively influence to bean weight. Chlorophyll total (a+b) showed high genetic variance (σg2), high phenotypic variance (σf2) and high estimated value of heritability (H). The chlorophyll a,b had moderate genetic variance, moderate phenotypic variance and high of estimated value of heritability. Chlorophyll total (a+b) could be used a selection criteria based on the value of correlation, genetic variance, phenotypic variance and estimated value of heritability would give high opportunity in selection process.